2013
DOI: 10.3109/14397595.2013.844390
|View full text |Cite
|
Sign up to set email alerts
|

Serum interleukin 6 levels as a useful prognostic predictor of clinically amyopathic dermatomyositis with rapidly progressive interstitial lung disease

Abstract: Serum IL-6 levels may predict the prognosis of CADM patients with RP-ILD. The intensity of immunosuppressive treatment can be decided according to serum IL-6 levels at an early phase of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 16 publications
1
21
1
Order By: Relevance
“…Upregulated IL-6 production stimulated by PGRN [27,28,45] may be related to elevation of CRP in DM patients with A/SIP. Serum IL-6 levels were significantly higher in dead than alive CADM patients with ILD [33] and were reported to be candidate biomarkers for disease activity in DM [32] and SLE [46]. Because TLR9 is highly expressed in DM [29-31] and SLE [47], upregulated IL-6 production stimulated by PGRN via TLR9 may be a common pathogenesis of DM and SLE.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulated IL-6 production stimulated by PGRN [27,28,45] may be related to elevation of CRP in DM patients with A/SIP. Serum IL-6 levels were significantly higher in dead than alive CADM patients with ILD [33] and were reported to be candidate biomarkers for disease activity in DM [32] and SLE [46]. Because TLR9 is highly expressed in DM [29-31] and SLE [47], upregulated IL-6 production stimulated by PGRN via TLR9 may be a common pathogenesis of DM and SLE.…”
Section: Discussionmentioning
confidence: 99%
“…Positive anti-MDA5 antibody, high serum ferritin level, and high serum IL-6 level before treatment were previously reported as prognostic factors of DM-IP 1621, 29 . Although serum IL-6 was not examined in this study, the anti-MDA5 antibody-positive rate was higher in the death group, similar to findings in previous reports.…”
Section: Discussionmentioning
confidence: 80%
“…Interferon-α, tumor necrosis factor-α, interleukin (IL)-6, IL-10, and IL-18 were related to disease activity 20, 2632 . Patients with a high serum IL-6 level had a poor prognosis 29 . Chemokines induce directed chemotaxis and activation of various leukocytes and relate to the pathophysiological conditions of several diseases including DM-IP.…”
Section: Introductionmentioning
confidence: 99%
“…A high KL–6 level, anti-MDA5 Ab positivity, high serum levels of ferritin, IL–6, IL–10, and IL–8, and a high level of AaDO 2 have been reported as serological factors in DM-IP that indicate a poor prognosis [ 33 35 , 36 39 ]. Sato et al reported that anti-MDA5 Ab is a useful prognostic indicator of DM-IP [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the patients in all of the fatal cases in our study were anti-MDA5 Ab-positive. Nara et al reported that the serum IL–6 level was 9 pg/ml or higher in all 6 patients with CADM-IP who died of IP, whereas it was lower than 9 ng/ml in 5 of 6 survivors [ 39 ]. It has also been reported that in patients with DM-IP, those with a serum ferritin level ≥ 1500 ng/ml, or those with a serum ferritin level ≥ 600 ng/ml plus AaDO 2 ≥ 45 mmHg, have poor prognoses [ 8 , 33 ].…”
Section: Discussionmentioning
confidence: 99%